PENINGKATAN PHBS MELALUI PENYEDIAAN SARANA KESEHATAN GIGI DI SD GMIT PARITI - Ratu, Antonius R.; Manu, Apri A.; Wali, Agusthinus; Obi, Applonia L. (MAJU : Indonesian Journal of Community Empowerment, 2025)
Dental health problems experienced by school-aged children are very complex and varied. Dental and oral health problems in school-aged children are currently quite worrying. Dental and oral hygiene is an indicator that can influence a person's dental and oral health status and even general health status. Tooth brushing behavior is one of the efforts made by every individual to prevent dental and oral diseases. There are many factors that can cause a person's dental and oral health status to be good or bad, including knowledge, behavior and the availability of dental and oral health facilities which also play a role in a person's dental and oral health status. The results of measuring the dental and oral hygiene status of students in grades IV and V at SD GMIT Pariti show that there are still many students whose dental and oral hygiene status is not good. For this reason, efforts are made to increase knowledge and skills in efforts to maintain dental and oral health through counseling and demonstrations of good and correct tooth brushing as well as providing facilities for clean and healthy living behavior in the field of dental and oral health. The results of the activity show that there is the ability to take self-care measures in the field of dental and oral health so that it influences the status of dental and oral hygiene as well.